REPRESENTASI ISLAM MODERAT DALAM FILM BULAN TERBELAH DI LANGIT AMERIKA - Mitha Oktopiana; Nita Rimayanti (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2018)
The number of radical groups such as terrorism in the name of Islam makes the face of Islam is getting tarnished, in fact Islam is a moderate religion which is moderate among extreme understandings, to convey the message of moderate Islam is one of them through the movie. The aims of the study to determine the meaning of denotation, connotation, and myth in the film of the Split Moon in the Sky of America, and to know the Representation of Islam Moderate in the Split Moon in the Sky of America. This research used qualitative method through semiotics analysis Roland Barthes, data collection techniques used in this research is through technique observation, documentation and literature study. The data used in the form of primary data sourced from the Split Moon Movie in the Sky of America , and secondary data obtained from library books, notes and documentation of the Split Moon in the Sky America, information from the internet and others concerned with the Split Moon movie in the Sky of America. The Results of this research focused on dialogue and visuals using analysis semiotics of Roland Barthes, found the denoted meaning of moderate Islam described in the film The Moon Splits in the sky of America is a form of moderate Islamic behavior in daily life in American society after the bombing in the building WTC, the meaning of moderate Islamic connotation in this film are the behaviors that should be done by moderate Islam in the face of various problems that occur in society, and the myths represented in this film are characteristic or moderate Islamic traits of them, adjust to the environment, friendly, patient, friendly with anyone, defending his faith, help, forgiveness and can coexist with non-Muslims and equally maintain harmony. Representation The moderate Islam in Split the Moon in the Sky is a moderate Islam is a religion that can adapt to the environment and culture certain, friendly and friendly, patient and forgiving, please help and be alive side by side and maintain harmony among religious people. Keyword:representation, Film, Semiotic, Islam